Stress-Induced Legume Root Nodule Senescence. Physiological, Biochemical, and Structural Alterations - Matamoros, Manuel A. (American Society of Plant Physiologists, 1999)
Nitrate-fed and dark-stressed bean (Phaseolus vulgaris) and pea (Pisum sativum) plants were used to study nodule senescence. In bean, 1 d of nitrate treatment caused a partially reversible decline in nitrogenase activity and an increase in O(2) diffusion resistance, but minimal changes in carbon metabolites, antioxidants, and other biochemical parameters, indicating that the initial decrease in nitrogenase activity was due to O(2) limitation. In pea, 1 d of dark treatment led to a 96% decline in nitrogenase activity and sucrose, indicating sugar deprivation as the primary cause of activity loss. In later stages of senescence (4 d of nitrate or 2–4 d of dark treatment), nodules showed accumulation of oxidized proteins and general ultrastructural deterioration. The major thiol tripeptides of untreated nodules were homoglutathione (72%) in bean and glutathione (89%) in pea. These predominant thiols declined by approximately 93% after 4 d of nitrate or dark treatment, but the loss of thiol content can be only ascribed in part to limited synthesis by γ-glutamylcysteinyl, homoglutathione, and glutathione synthetases. Ascorbate peroxidase was immunolocalized primarily in the infected and parenchyma (inner cortex) nodule cells, with large decreases in senescent tissue. Ferritin was almost undetectable in untreated bean nodules, but accumulated in the plastids and amyloplasts of uninfected interstitial and parenchyma cells following 2 or 4 d of nitrate treatment, probably as a response to oxidative stress.